2005
DOI: 10.1055/s-2005-922747
|View full text |Cite
|
Sign up to set email alerts
|

Design and Synthesis of Novel TrichloromethylatedN-Azolylmethyl-1H-­pyrimidin-2-ones and RelatedN-Methylenaminones

Abstract: Reaction of 4-trichloromethyl-1H-pyrimidin-2-ones with 5-bromo-1,1,1-trichloro(fluoro)-4-methoxy-alk-3-en-2-ones affords 1-[5,5,5-trichloro(fluoro)-2-methoxy-4-oxopent-2-en-1-yl]-4-trichloromethyl-1H-pyrimidin-2-ones. Reaction of the latter trichloromethylated compound with amines, hydroxylamine, and hydrazines affords a series of 1-(2-alkylamine-5,5,5-trichloro-4-oxopent-2-en-1-yl)-4-trichloromethyl-1H-pyrimidin-2-ones and 1-(5-trichloromethyl-5-hydroxy-4,5-dihydro-3-azol-3-ylmethyl)-4-trichloromethyl-1H-pyri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 8 publications
0
20
0
Order By: Relevance
“…Compound 56 was reacted with brominated enone 4 , which furnished only the N ‐alkylated derivative 57 , at a moderate yield (60 %, Scheme 16). [75] The N ‐alkylated pyrimidin‐2(1 H )‐one 57 was evaluated against leukemia and human melanoma cell lines, and the mechanism for the anticancer activity was also investigated. It was observed that 57 stimulated cell death by apoptosis, which was evidenced by DNA fragmentation, phosphatidylserine externalization, and caspase‐3 activation.…”
Section: Synthesis Of Pyrimidines Using Ncn‐dinucleophilesmentioning
confidence: 99%
“…Compound 56 was reacted with brominated enone 4 , which furnished only the N ‐alkylated derivative 57 , at a moderate yield (60 %, Scheme 16). [75] The N ‐alkylated pyrimidin‐2(1 H )‐one 57 was evaluated against leukemia and human melanoma cell lines, and the mechanism for the anticancer activity was also investigated. It was observed that 57 stimulated cell death by apoptosis, which was evidenced by DNA fragmentation, phosphatidylserine externalization, and caspase‐3 activation.…”
Section: Synthesis Of Pyrimidines Using Ncn‐dinucleophilesmentioning
confidence: 99%
“…29 N-Alkyl-1,1,1-trichloro-5-pyrimidinyl-enaminones 26 were furnished in 70-98% yields using secondary amines under the same conditions. 30 Reaction of 24 with dinucleophiles such as hydroxylamine hydrochloride or phenylhydrazine in MeOH for 16 h at reflux gave isoxazoles 27 (Y = O) and pyrazoles 27 (Y = NR 3 ) conjugated with the pyrimidin-2(1H)-one core in 60-80% yields. 30 When o-phenylenediamine in EtOH for 4 h at reflux was used, the benzimidazole derivative 28 was obtained, probably by a retro-aldol mechanism (Scheme 6).…”
Section: Short Review Syn Thesis 3 Synthesis Using First-generation Imentioning
confidence: 99%
“…30 Reaction of 24 with dinucleophiles such as hydroxylamine hydrochloride or phenylhydrazine in MeOH for 16 h at reflux gave isoxazoles 27 (Y = O) and pyrazoles 27 (Y = NR 3 ) conjugated with the pyrimidin-2(1H)-one core in 60-80% yields. 30 When o-phenylenediamine in EtOH for 4 h at reflux was used, the benzimidazole derivative 28 was obtained, probably by a retro-aldol mechanism (Scheme 6). It is important to note that compound 24 exhibited a high level of anticancer activity against human leukemia and melanoma cell lines.…”
Section: Short Review Syn Thesis 3 Synthesis Using First-generation Imentioning
confidence: 99%
“…In 2005, Zanatta et al [61], exploring the synthetic usefulness of a series of trihalomethylated N-enonylmethylpyrimidin-2-ones, synthesized the 5-trichloromethyl-5hydroxy-4,5-dihydroisoxazolylmethyl pyrimidinone. The Nenonylmethylpyrimidin-2-one 54 reacted with hydroxylamine hydrochloride in the presence of pyridine, methanol, under reflux for 24 h, furnishing the N-methylene-(4,5dihydroisoxazol-3-yl)pyrimidinone derivative 55 in 80% yield (Scheme 19).…”
Section: -Halomethyl-5-hydroxy-45-dihydroisoxazolesmentioning
confidence: 99%